Wealth and welfare across generations - David Sturrock (Institute for Fiscal Studies (IFS), 2023)
Although older generations have substantially more wealth than their recent predecessors did at the same age, younger generations do not. Bringing together UK data on those born between the 1930s and 1980s and a lifecycle model of saving, I quantify whether this is due to changes in preferences or changes in the circumstances each generation has faced. Changing circumstances can rationalise slowing generation-on-generation wealth growth. I find no evidence that later-born generations are less patient. I quantify the implications of changing circumstances for consumption and welfare. Later-born generations are predicted to have higher consumption, despite accumulating no greater wealth, than their predecessors because their earnings are more 'backloaded', they have fewer children, and face lower taxation.
Keywords: D15; D31; E21; E24; 330; ntergenerational inequality; wealth accumulation; lifecycle